Pengaruh Bimbingan Kelompok Teknik Role Playing Terhadap Komunikasi Interpersonal Siswa Kelas XI Broadcast 2 SMK N 1 Semarang - Adhesty, Yulia Niken (MEDI KONS: Jurnal Prodi Bimbingan dan Konseling UNISRI Surakarta, 2023)
Communication plays an important role in the world of education, any information conveyed to students can be captured by students if the student is able to understand the information conveyed. This is what causes how important it is to learn to communicate, at school students learn to be able to communicate with others through many things such as discussions and role playing. Just like at school, students will communicate with other people every day. In this study, researchers used a quasi-experimental design quantitative research model. This study used a pre-test post-test control group design. Before being given treatment, students are first given a pre-test. The results of the pre-test between the control group and the experiment showed that there was a significant difference between the control group and the experiment. The average interpersonal communication of students in the control group was 105.3 for the experimental group of 105.6. The difference between the two groups is 0.3, it can be said that there is a significant difference. The results of the tests that have been carried out can be seen that the results of the significance of the hypothesis show 0.002<0.05. So the hypothesis reads that there is an influence of group guidance with role playing techniques on the communication of class XI BROADCAST 2 SMK N 1 Semarang students.Key Words: Group conseling, Interpersonal comunication, Role playing